Human Rights in Islam: A Way towards Justice for Humanity - Wani, Hilal Ahmad; Suwirta, Andi (ASPENSI in Bandung, Indonesia, 2013)
ABSTRACT: Islam is complete code of life, because there is not any single dimension related to human beings which had not been touched and included. Before 14 hundred years, Muslims had human rights; so, saying that human rights are kind of new phenomenon and a new package for humanity, it is wrong and unjustified. This paper is based on strong research data to challenge all anti Islamic views and notions about the Islam. To examine the bunch of rights which Islam had given to human beings from the very beginning, even before the so called genesis of world human rights. And to justify that Islam is the real custodian and guardian of human rights for every human being. And to prove that all anti-Islamic challenges are nothing, but a chimera and myth of the anti-Islamic forces on Islam and Muslims so that they could be successful to mould the people against Islam and Muslim world, whereas Islam is divine religion supported by Allah, the anti-Islamic forces cannot hurt Islam because Islam is based on universal and human principles which cannot be challenged by someone who does not have vision to understand the real philosophy of Islam. Islam is the real solution to the world, a world where justice is totally absent. Islam is the real voice of oppressed and suppressed people and it is a true way for justice and world brotherhood.KEY WORD: Code of life, Islam, human rights, justice, humanity, world order, Islamic forces, and Muslim countries. Â Â RESUME: Makalah ini berjudul âHak Azasi Manusia dalam Islam: Sebuah Jalan Menuju Keadilan bagi Kemanusiaanâ. Islam merupakan pedoman hidup yang lengkap, karena tidak ada satupun dimensi yang berhubungan dengan manusia yang tidak tersentuh dan tercakup. Sebelum 1400 tahun, umat Islam memiliki hak asasi manusia; maka, perkataan bahwa hak asasi manusia merupakan fenomena baru dan suatu kemasan baru bagi kemanusiaan merupakan hal yang salah dan tidak berdasar. Makalah ini berdasarkan data penelitian yang kuat untuk menantang semua pandangan anti Islam dan keyakinan tentang Islam. Untuk menguji seperangkat hak-hak yang telah diberikan Islam kepada umat manusia mulai dari awal, bahkan sebelum disebut dalam hak asasi manusia dunia. Dan juga untuk meyakinkan bahwa Islam merupakan pemelihara dan pelindung hak asasi manusia bagi setiap umat manusia. Dan untuk membuktikan bahwa semua tantangan anti Islam tidak ada artinya, melainkan gagasan yang tidak masuk akal dan mitos tentang kekuatan-kekuatan anti Islam terhadap Islam dan kaum Muslim sehingga mereka bisa berhasil untuk menciptakan orang-orang yang menentang Islam dan dunia Muslim, sebaliknya Islam merupakan agama yang hebat dan didukung oleh Allah, kekuatan-kekuatan anti Islam tidak dapat mencederai Islam karena Islam berlandaskan prinsip-prinsip universal dan kemanusiaan yang tidak bisa ditentang oleh seseorang yang tidak memiliki visi untuk memahami filosofi Islam yang sesungguhnya. Islam merupakan solusi nyata bagi dunia, suatu dunia dimana keadilan benar-benar tidak ada. Islam merupakan suara nyata dari orang-orang tertindas dan tertekan dan ianya merupakan jalan yang benar bagi keadilan dan persaudaraan dunia.KATA KUNCI: Pedoman hidup, Islam, hak azasi manusia, keadilan, kemanusiaan, ketertiban dunia, kekuatan Islam, dan negeri-negeri Muslim.Â Â About the Authors: Dr. Hilal Ahmad Wani is a Post-Doctoral Fellow at the Centre for Peace and Strategic Studies UOI (University of Ilorin) in Nigeria; and Andi Suwirta, M.Hum. is a Senior Lecturer at the Department of History Education UPI (Indonesia University of Education) in Bandung, West Java, Indonesia. They can be reached at: wanihilal@gmail.com and andisuwirta@yahoo.com Â How to cite this article? Wani, Hilal Ahmad & Andi Suwirta. (2013). âHuman Rights in Islam: A Way towards Justice for Humanityâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.6, No.1 [Mei], pp.1-12. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (March 11, 2013); Revised (April 13, 2013); and Published (May 20, 2013). Â Â